Prepectoral Versus Retropectoral Implant-Based Breast Reconstruction: Equivalent Safety with Improved Long-Term Implant Durability - Falkenberg, Varpu (My University, 2026)
While implant-based breast reconstruction (IBBR) is the most frequently performed procedure following mastectomy, the optimal surgical approach remains debated. The retropectoral (RP) technique has been the historical standard, but prepectoral (PP) reconstruction is increasingly adopted. Nevertheless, a lack of long-term data comparing complications of these techniques exists. The objective of this study was to perform a comparative analysis of clinical outcomes for prepectoral versus retropectoral IBBR. A retrospective review was conducted of 139 patients who underwent prepectoral (n=86) or retropectoral (n=53) IBBR between 2009-2024. Patient demographics, comorbidities, oncologic history, and treatment data were abstracted from institutional records. Primary outcomes included surgical site complications, reoperations, and implant revision rates at follow-up. The overall postoperative complication rate was similar between the groups. Early and late reoperation rates were also comparable. However, a strong trend toward a higher late implant exchange rate was observed in the subpectoral cohort. Immediate reconstruction, radiotherapy, and higher ASA scores were identified as significant independent predictors of postoperative complications. Bilateral reconstruction and higher BMI demonstrated a trend toward significance. This study demonstrates that prepectoral IBBR is a safe and viable alternative to the traditional subpectoral approach. The strong trend toward a higher late implant exchange rate in the subpectoral group suggests a potential advantage for the prepectoral technique in long-term implant durability. Ultimately, patient selection remains paramount: independent risk factors matter more than the choice of surgical plane. These findings support the continued adoption of the prepectoral technique while highlighting the need for careful preoperative risk assessment.
Keywords: implant based; immediate breast reconstruction; prepectoral; retropectoral; postoperative complications